2021
DOI: 10.1177/00033197211053902
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Pancreas Disease: A Diagnosis of Increasing Importance

Abstract: In this issue of Angiology, Sahin and Karadeniz report the results of their study involving 183 patients with hepatic steatosis (HS) diagnosed by transabdominal ultrasonography. 1 Among these patients, 85 (46.5%) also had non-alcoholic fatty pancreas disease (NAFPD). Patients with both HS and NAFPD exhibited significantly greater carotid intima media thickness (cIMT), a marker of early atherosclerosis, compared with patients with HS only. Age, hypertension and the presence of NAFPD were independent predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In general, fat deposition is linked to multiple diseases like metabolic syndrome, diabetes, and atherosclerosis. 2,76 In a large cross-sectional study where NAFPD and its risk factors were examined, authors compared pancreatic echogenicity with that of the liver and demonstrated that fatty pancreas and fatty liver composition were found in combination in almost 26% of patients, whereas fatty pancreas alone was found in 16%. 11 In a prospective study almost 68% of the included patients with fatty pancreas presented with fatty liver, but 97% of patients initially diagnosed with fatty liver presented concurrently with a fatty pancreas, making fatty liver a strong predictive factor of fatty pancreas disease.…”
Section: Clinical Associations Of Nafpd Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In general, fat deposition is linked to multiple diseases like metabolic syndrome, diabetes, and atherosclerosis. 2,76 In a large cross-sectional study where NAFPD and its risk factors were examined, authors compared pancreatic echogenicity with that of the liver and demonstrated that fatty pancreas and fatty liver composition were found in combination in almost 26% of patients, whereas fatty pancreas alone was found in 16%. 11 In a prospective study almost 68% of the included patients with fatty pancreas presented with fatty liver, but 97% of patients initially diagnosed with fatty liver presented concurrently with a fatty pancreas, making fatty liver a strong predictive factor of fatty pancreas disease.…”
Section: Clinical Associations Of Nafpd Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Pancreatic fat deposition in the absence of excessive alcohol intake, described as non-alcoholic fatty pancreas disease (NAFPD), 1 is an emerging clinical entity. 2 Despite the higher susceptibility to fat deposition of the pancreas compared to the liver, 3,4 the clinical relevance and underlying pathophysiological mechanisms of pancreatic fat infiltration remain unclear in the medical literature. Robertson F. Ogilvie was the first to describe pancreatic fat deposition in obese cadavers, reporting 17% of pancreatic fat storage, as compared to 9% in lean ones.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of oxidative stress, an increase in free fatty acid transport to the pancreas by very-low-density lipoprotein and changes in various adipokines such as adiponectin, 36 lipocalin-2, 37 and hepatokine fetuin-A 38 via the serine/threonine-protein kinase 25 (STK-25) pathway may contribute to this type of pancreatic fat accumulation. 39…”
Section: Pathophysiology Of Pancreatic Fat Accumulationmentioning
confidence: 99%
“…Available evidence from experimental models and human studies suggests a bidirectional relationship between fatty pancreas and NAFLD. 6,19,24,39…”
Section: Links Between Fatty Pancreas and Nafldmentioning
confidence: 99%